Symmetry breaking of the cellular lobes closely relates to phylogenetic structure within green microalgae of the Micrasterias lineage (Zygnematophyceae) - Neustupa, Jiri; Stastny, Jan (PeerJ, 2018)
Green microalgae of the Micrasterias lineage are unicellular microorganisms with modular morphology consisting of successively differentiated lobes. Due to their morphological diversity and peculiar morphogenesis, these species are important model systems for studies of cytomorphogenesis and cellular plasticity. Interestingly, the phylogenetic structure of the Micrasterias lineage and most other Desmidiales is poorly related to the traditional morphological characters used for delimitation of taxa. In this study, we focused on symmetry breaking between adjacent cellular lobes in relation to phylogeny of the studied species. While pronounced morphological asymmetry between the adjacent lobes is typical for some species, others have been characterized by the almost identical morphologies of these structures. We asked whether there is any detectable average shape asymmetry between the pairs of lobes and terminal lobules in 19 Micrasterias species representing all major clades of this desmidiacean lineage. Then, we evaluated whether the asymmetric patterns among species are phylogenetically structured. The analyses showed that the phylogeny was in fact strongly related to the patterns of morphological asymmetry between the adjacent cellular lobes. Thus, evolution of the asymmetric development between the adjacent lobes proved to be the key event differentiating cellular shape patterns of Micrasterias. Conversely, the phylogeny was only weakly related to asymmetry between the pairs of terminal lobules. The subsequent analyses of the phylogenetic morphological integration showed that individual hierarchical levels of cellular morphology were only weakly coordinated with regard to asymmetric variation among species. This finding indicates that evolutionary differentiation of morphogenetic processes leading to symmetry breaking may be relatively independent at different branching levels. Such modularity is probably the key to the evolvability of cellular shapes, leading to the extraordinary morphological diversity of these intriguing microalgae.
Keywords: Asymmetry; Phylomorphospace; Phenotype evolution; Cytomorphogenesis; Geometric morphometrics; Desmidiales